Transcriptome analysis of Listeria monocytogenes exposed to biocide stress reveals a multi-system response involving cell wall synthesis, sugar uptake, and motility - Casey, Aidan; Fox, Edward M.; Schmitz-Esser, Stephan; Coffey, Aidan; McAuliffe, Olivia; Jordan, Kieran (Frontiers in Microbiology, 2014)
Listeria monocytogenes is a virulent food-borne pathogen most often associated with the consumption of ‘ready-to-eat’ foods. The organism is a common contaminant of food processing plants where it may persist for extended periods of time. A commonly used approach for the control of Listeria monocytogenes in the processing environment is the application of biocides such as quaternary ammonium compounds. In this study, the transcriptomic response of a persistent strain of L. monocytogenes (strain 6179) on exposure to a sub-lethal concentration of the quaternary ammonium compound benzethonium chloride (BZT) was assessed. Using RNA-Seq, gene expression levels were quantified by sequencing the transcriptome of L. monocytogenes 6179 in the presence (4 ppm) and absence of BZT, and mapping each data set to the sequenced genome of strain 6179. Hundreds of differentially expressed genes were identified, and subsequent analysis suggested that many biological processes such as peptidoglycan biosynthesis, bacterial chemotaxis and motility, and carbohydrate uptake, were involved in the response of L. monocyotogenes to the presence of BZT. The information generated in this study further contributes to our understanding of the response of bacteria to environmental stress. In addition, this study demonstrates the importance of using the bacterium’s own genome as a reference when analysing RNA-Seq data.